The Role of Congestion-Adaptive Routing Protocol in Mobile Ad Hoc Networks - Vijay Uttam Rathod; Shyamrao Vasantrao Gumaste; Himadri Majumder (The Scientific World Journal)
In MANETs, the congestion-adaptive routing protocol (CRP) enhances data delivery by dynamically adjusting routes based on real-time congestion, unlike traditional protocols that lack congestion adaptability. The present paper discusses the CRP proposed protocols for evaluating the E2E delay, PDR, overhead, and energy consumption across various data rates (1–40) and communication times (0–900 ms) using the ns-3 simulator. The obtained results were compared with the DSR, TORA, OLSR, and AODV protocols. Results indicate that CRP delivers superior performance to DSR, TORA, OLSR, and AODV in congestion-aware conditions. The optimal improvements in the CRP protocol are observed for an E2E delay of 85% and a PDR of 53.84%. In the case of routing overhead and energy consumption, the performance of the CRP protocol has been reduced by 20.68% and 23.07%, respectively, compared to the DSR and AODV protocols.